Penggunaan Umpan Balik Rekan Sebaya terhadap Evaluasi Diri dan Efikasi Diri dalam Keterampilan Menulis - Samuel Adhi; Fransisca I. R. Dewi; Fidelis E. Waruwu (Provitae: Jurnal Psikologi Pendidikan, 2012)
This research was based on Bandura’s system of triadic reciprocal causation in social cognitive concept. The research was designed to test the hypothesis that the usage of different type of peer feedback (as an enviroment factor) has a different effect in increasing students’ self-evaluation (as a behavioural factor) and selfefficacy (as a personal factor) in writing skills learning situation. The research design was pre-test post-test control group design. Sixty six subjects participated in three equal classes divided into two groups. First group consisted of two experimental classes which stood for two types of feedback (formated and unformated) and one control group with placebo. The results showed that there was a significant effect of peer feedback type (formated and unformated) to increase student self-evaluation and self-efficacy in writing skills. Differences in self-evaluation scores F(2.63) = 37.506, (p <0.05), and self-efficacy F(2.63) =7.272, (p < 0.05). Skills writing students in the experimental group was higher than in the control group. The results also showed differences in the usage of the type of feedback and free peer to increased self-evaluation unformated, however there was no difference in the improvement of self-efficacy students.Keywords: peer feedback, students’ self-evaluation, self-efficacy in writing skills learning context